2016
DOI: 10.1242/dmm.024745
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine IL-10 activation of the STAT3 pathway is required for pathological macrophage differentiation in polycystic kidney disease

Abstract: Polycystic kidney disease (PKD) is characterized by slow expansion of fluid-filled cysts derived from tubules within the kidney. Cystic expansion results in injury to surrounding parenchyma and leads to inflammation, scarring and ultimately loss of renal function. Macrophages are a key element in this process, promoting cyst epithelial cell proliferation, cyst expansion and disease progression. Previously, we have shown that the microenvironment established by cystic epithelial cells can ‘program’ macrophages,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 41 publications
(73 reference statements)
1
19
0
Order By: Relevance
“…The signals from lactate that elicit M2-like functional polarization of TAMs are still not fully understood. Many signals are involved in M2-like macrophage polarization, for instance, ERK1/2, STAT3, HIF1a, and STAT6 and so forth, the activation of which can upregulate M2 macrophage polarization via different ways in the TME [5,15]. In this study, we found that lactate activated ERK1/2 and STAT3 signaling in macrophages.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The signals from lactate that elicit M2-like functional polarization of TAMs are still not fully understood. Many signals are involved in M2-like macrophage polarization, for instance, ERK1/2, STAT3, HIF1a, and STAT6 and so forth, the activation of which can upregulate M2 macrophage polarization via different ways in the TME [5,15]. In this study, we found that lactate activated ERK1/2 and STAT3 signaling in macrophages.…”
Section: Discussionsupporting
confidence: 52%
“…Macrophages in the tumor microenvironment can be educated by cancer cells [15]. To examine whether cancer cell-derived lactate can modulate macrophage M2 activation, Western blot and QPCR analyses of bone marrow-derived macrophages (BMDMs) and the THP-1 cell line showed that lactate enhanced the expression of M2 macrophage markers.…”
Section: Tumor-derived Lactate Induced M2 Macrophage Polarizationmentioning
confidence: 99%
“…3 Although the proproliferative function of macrophages in connection with cyst-lining epithelial cells (CLECs) has been explored in a few studies, the specific mechanism remains unclear. [4][5][6] Macrophages are not homogenous, and they are generally categorized into two distinct phenotypes: classically activated (M1) or alternatively activated (M2). 7 ARG1 is a classic M2-like molecular marker for macrophages and abundant M2-type macrophages are detected in polycystic kidney tissue.…”
mentioning
confidence: 99%
“…In this paper we find that curcumin targets JAK2 by causing it to become inactive leading to reduced STAT3 activity. Given that STAT3 may be cystogenic, (8,25,30,31), it stands to speculate that some of the protection offered by curcumin may be via inhibition of STAT3 activity. However, high doses of curcumin are needed to inhibit STAT3, as shown in our study (25-100μM) and gaining these concentrations in plasma is difficult, given curcumin’s reduced bioavailability (24).…”
Section: Discussionmentioning
confidence: 99%